Oral Administration of Acrylamide Worsens the Inflammatory Responses in the Airways of Asthmatic Mice Through Agitation of Oxidative Stress in the Lungs - Hajimohammadi, Bahador; Athari, Seyyede Masoume; Abdollahi, Mohammad; Vahedi, Ghasem; Athari, Seyyed Shamsadin (Frontiers in Immunology, 2020)
Acrylamide is a toxic chemical substance when starch-rich foods are fried at high temperature, acrylamideAA is formed in the food. Asthma is one of the chronic and complicated respiratory disease that genetic and environmental factors are main triggers of asthma. Oral received components may have effect on the asthma pathophysiology. The aim of this study was to investigate the role of acrylamide AA as a stimulus in asthma. BALB/c mice were allocated into four groups as followings; two OVA-sensitized asthmatic groups, including one treated with AA by gavage feeding and one non-treated (asthma group) and also two healthy (non-asthmatic) groups; one treated with AA by gavage feeding and one non-treated (negative control group). Airway hyperresponsiveness, cell count and cytokines level in BAL fluid, lung histopathology, IgE levels and oxidative stress indices including plasma level of MDA, pulmonary antioxidant enzymes (SOD and CAT) levels, HP content in lung and collagen fibers accumulation in lung tissue were measured. We found that the group of mice treated with both OVA and AA (asthmatic and acrylamideAA-treated mice) has experienced higher levels of asthma-associated biomarkers including; higher enhanced pause (Penh value), eosinophilic inflammation, mucus hyper-secretion, goblet cell hyperplasia, total and OVA-specific IgE levels, and IL-4, IL-5 and IL-13 levels than the group sensitized only with OVA (asthmatic mice). The OVA-AA-treated mice also experienced the worsened levels of oxidative stress indicators. Healthy (non-asthmatic) mice that only received AA were in similar conditions to healthy untreated mice (negative control group). OVA-AA-treated group showed more severe allergic asthma symptoms in comparison to the group only sensitized with OVA. Therefore, the food/water contaminated with AA can act as a stimulant of allergic asthma and exacerbate the bronchial inflammatory responses.